Multi-user detection for multi-carrier communication systems - Hijazi, Samer L. (Kansas State University, 2006)
Wireless broadband communications is a rapidly growing industry. New enabling technologies such as multi-carrier code division multiple access (MC-CDMA) are shaping the future of wireless systems. However, research efforts in improving MC-CDMA receiver performance have received limited attention and there is a need for innovative receiver designs for next generation MC-CDMA. In this thesis, we propose novel multi-user detection (MUD) schemes to enhance the performance of both synchronous and asynchronous MC-CDMA. First, we adapt the ant colony optimization (ACO) approach to solve the optimal MUD problem in MC-CDMA systems. Our simulations indicate that the ACO based MUD converges to the optimal BER performance in relatively few iterations providing more that 95% savings in computational complexity. Second, we propose a new MUD structure specifically for asynchronous MC-CDMA. Previously proposed MUDs for asynchronous MC-CDMA perform the detection for one user (desired user) at a time, mandating multiple runs of the algorithm to detect all users' symbols. In this thesis, for the first time we present a MUD structure that detects all users' symbols simultaneously in one run by extending the receiver's integration window to capture the energy scattered in two consecutive symbol durations. We derive the optimal, decorrelator and minimum mean square error (MMSE) MUD for the extended window case. Our simulations demonstrate that the proposed MUD structures not only perform similar to a MUD that detects one user at a time, but its computational complexity is significantly lower. Finally, we extend the MUD ideas to multicarrier implementation of single carrier systems. Specifically, we employ the novel MUD structure as a multi-symbol detection scheme in CI-CDMA and illustrate the resulting performance gain via simulations.
Keywords: Multiuser detection; Multicarrier; Engineering, Electronics and Electrical (0544)